Henry's clinical diagnosis and management by laboratory methods - McPherson, Richard A.; Pincus, Matthew R.; Henry, John Bernard (Elsevier/Saunders, 2011)
A comprehensive, multidisciplinary pathology reference that gives you guidance on lab test selection and interpretation of results.